SOCIO ENVIRONMENTAL FACTORS ASSOCIATED WITH THE SELECTION OF CONTRACEPTIVES IN GADING PUBLIC HEALTH CENTER TAMBAKSARI SURABAYA (Proceedings of the International Conference on Public Health, 2017)
Long-term contraception methods have entered into goverment programs to effectively postpone pregnancy, space births and terminate fertility. However, Women of fertile ages(15-49 years old) in Indonesia were still likely  to choose short-term contraceptives, especially injectable contraceptive. This research analyzed the social environmental factors relating the selection of contraceptives in Gading Public Health Center Tambaksari Surabaya. This research used analitycal methods with case control study. The sampling technique used simple random sampling to procure cases and controls, and got 42 of each.The variables were socio environmental factors.Data were analyzed using multivariate logistic regression with a level of significance value α = 0,05. The results showed five significant variables were the role of the spouse (p=0,002), the role of family (p=0,001), the role of health care workers  (p=0,011), the role of community leaders (p=0,0018), and the role of print media  (p=0,015). Social environmental factors included the role of spouse, health care workers, community leaders and print media associated with the selection of contraceptives in Gading Public Health Center Tambaksari Surabaya. The provision of support and complete information about all types of contraception are important so that the women of fertile ages can choose contraception that suits their needs.
Keywords: family planning, Long-Term Contraception Methods